Live reptile smuggling is predicted by trends in the legal exotic pet trade. Issue 6 (17th August 2021) - Stringham, Oliver C.; García‐Díaz, Pablo; Toomes, Adam; Mitchell, Lewis; Ross, Joshua V.; Cassey, Phillip
Abstract: Live animal smuggling presents a suite of conservation and biosecurity concerns, including the introduction of invasive species and diseases. Yet, understanding why certain species are smuggled over others, and predicting which species will be smuggled, remains relatively unexplored. Here, we compared the live reptile species illegally smuggled to Australia (75 species) to the legal trade of live reptile species in the United States. Almost all smuggled species were found in the legal US pet market (74 species), and we observed an average time lag of 5.6 years between a species first appearing in the United States and its subsequent detection in Australia. Using a Bayesian regression model, species popularity in the United States, and internationally, were positively associated with smuggling probability to Australia. Our findings give insight to the drivers of illegal wildlife trade and our predictive modelling approach provides a framework for anticipating future trends in wildlife smuggling.